2016
DOI: 10.1016/j.ijhydene.2015.10.151
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and first-principles DFT study on oxygen vacancies on cerium dioxide and its effect on enhanced photocatalytic hydrogen production

Abstract: Experimental and computational (DFT) approaches were carried out to investigate oxygen vacancies on Cerium dioxide. Computational result indicates oxygen vacancies can shorten the band gap of CeO 2 and enhance the absorption for visible light because Ce (III) created by generation of oxygen vacancies is easier for excitation than Ce (IV) under same irradiation. The order of calculated band gap for Ce 16 O 31 , (111) < (113) < (133), and the absorption data suggests that (111) plane may be the most ideal positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 36 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…For GO/Cu 2 O-0.5-af, the contents of C=O and C-O species decrease sharply because some organic groups like carboxyl and carbonyl can be degraded to carbon dioxide or other dissociative composition during visible light irradiation [41], and this decrease also enlarges the atomic percentages of C sp 2 and C sp 3 . But the percentages of C sp 2 are much larger than that of C sp 3 . By comparing the atomic compositions for GO/Cu 2 O-0.5 and GO/Cu 2 O-0.5-af (Table S1), it was found that the ratio of C sp 2 to C sp 3 increase from 0.86 to 1.22 while a part of covered GO was desquamated (Figure 7(D)) and the GO shell was thinner and more smooth (Figure 7(E)), which suggests that a part of sp 3 carbon was degraded during irradiation.…”
Section: Photocatalytic Mechanism Analysismentioning
confidence: 84%
See 2 more Smart Citations
“…For GO/Cu 2 O-0.5-af, the contents of C=O and C-O species decrease sharply because some organic groups like carboxyl and carbonyl can be degraded to carbon dioxide or other dissociative composition during visible light irradiation [41], and this decrease also enlarges the atomic percentages of C sp 2 and C sp 3 . But the percentages of C sp 2 are much larger than that of C sp 3 . By comparing the atomic compositions for GO/Cu 2 O-0.5 and GO/Cu 2 O-0.5-af (Table S1), it was found that the ratio of C sp 2 to C sp 3 increase from 0.86 to 1.22 while a part of covered GO was desquamated (Figure 7(D)) and the GO shell was thinner and more smooth (Figure 7(E)), which suggests that a part of sp 3 carbon was degraded during irradiation.…”
Section: Photocatalytic Mechanism Analysismentioning
confidence: 84%
“…Neither amounts of Cu (I) nor amounts of Cu (II) sharply decreased with the increasing of GO addition, which suggests that GO was formed on the surface rather than being mixed with the lattices of copper oxides. Meanwhile, both the atomic amount of sp 2 and sp 3 Band gap, conduction band edge and valence band edge are three important parameters for semiconductor photocatalysts, and they can be calculation form the UV-vis absorption spectra. The values of band gaps for Cu 2 O nanosphere and the GO-modified samples are estimated from the plot of the (αhν) 2 versus photon energy (hν) [4,38] as shown in Table 3.…”
Section: Characterization Of Go/cu 2 Omentioning
confidence: 99%
See 1 more Smart Citation
“…Due to these speciality, it is often used as a catalyst in various catalytic application such as solid oxide fuel cells (SOFCs), ultraviolet adsorbents, glass polishing materials, water gas shift reaction, PROX (CO oxidation), oxygen sensors, selective organic transformation, photocatalytic water oxidation and pollutant degradation [27,[39][40][41][42][43]. In addition to it, CeO 2 has other specialities such as cost-effectiveness, high stability, low toxicity and specific physical and chemical characteristics, such as high oxygen storage capacity (OSC), oxygen ion conductivity and fast shuttling of oxidation state (Ce 3+ K Ce 4+ ), which makes it an ideal candidate for photocatalysis [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59]. In brief, the rare earth CeO 2 has a crystal structure of triclinic or tetragonal or cubic phase.…”
Section: Introductionmentioning
confidence: 99%
“…The change is due to the oxygen vacancy, which creates a Ce 3+ state, thus the energy of 4f orbitals shift towards lower potential and hence shorten the bandgap. The density of state (DOS) of Ce4f for Ce(III) is larger than that of Ce(IV) in positive energy range, which indicates Ce(III) is easier for excitation than Ce(IV) under light irradiation, which suggests that oxygen vacancy enhances the visible light absorption [55]. In addition to the optical property, the oxygen vacancy of CeO 2 has also a profound effect on the electrical as well as magnetic character.…”
Section: Introductionmentioning
confidence: 99%